Serum Endocan as a Survival Predictor for Patients with Liver Cirrhosis - Nobuyuki Toshikuni; Kazuaki Ozaki; Joseph George; Mikihiro Tsutsumi (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: The relationship between endocan expression and outcome in patients with chronic liver disease is not fully understood.